Intercomparison of field measurements of nitrous acid (HONO) during the SHARP campaign. Issue 9 (5th May 2014) - Pinto, J. P.; Dibb, J.; Lee, B. H.; Rappenglück, B.; Wood, E. C.; Levy, M.; Zhang, R.‐Y.; Lefer, B.; Ren, X.‐R.; Stutz, J.; Tsai, C.; Ackermann, L.; et al.
Abstract Because of the importance of HONO as a radical reservoir, consistent and accurate measurements of its concentration are needed. As part of SHARP (Study of Houston Atmospheric Radical Precursors), time series of HONO were obtained by six different measurement techniques on the roof of the Moody Tower at the University of Houston. Techniques used were long path differential optical absorption spectroscopy (DOAS), stripping coil‐visible absorption photometry (SC‐AP), long path absorption photometry (LOPAP®), mist chamber/ion chromatography (MC‐IC), quantum cascade‐tunable infrared laser differential absorption spectroscopy (QC‐TILDAS), and ion drift‐chemical ionization mass spectrometry (ID‐CIMS). Various combinations of techniques were in operation from 15 April through 31 May 2009. All instruments recorded a similar diurnal pattern of HONO concentrations with higher median and mean values during the night than during the day. Highest values were observed in the final 2 weeks of the campaign. Inlets for the MC‐IC, SC‐AP, and QC‐TILDAS were collocated and agreed most closely with each other based on several measures. Largest differences between pairs of measurements were evident during the day for concentrations < 100 parts per trillion (ppt). Above 200 ppt, concentrations from the SC‐AP, MC‐IC, and QC‐TILDAS converged to within about 20%, with slightly larger discrepancies when DOAS was considered. During the first 2 weeks, HONO measured by ID‐CIMS agreed with these techniques, but ID‐CIMS reported higher values during the afternoon and evening of the final 4 weeks, possibly from interference from unknown sources. A number of factors, including building related sources, likely affected measured concentrations.